It’s time to change our documentation philosophy: writing better neurology notes without the burnout - Rodríguez-Fernández, Jorge M.; Loeb, Jeffrey A.; Hier, Daniel B. (Frontiers in Digital Health, 2022)
Succinct clinical documentation is vital to effective twenty-first century healthcare. Recent changes in outpatient and inpatient evaluation and management (E/M) guidelines have created an opportunity for neurology practices to make changes that minimize documentation burden and enhance clinical note usability. Despite favorable changes in E/M guidelines, some neurology practices have not moved quickly to change their documentation philosophy. We argue in favor of changes in the design, structure, and implementation of clinical notes that makes them shorter and more information-rich. A move from physician-centric to team documentation can reduce work for physicians. Changing documentation philosophy from "bigger is better" to "short but sweet" can reduce documentation burden, streamline the writing and reading of clinical notes, and enhance their utility for medical decision making, patient education, medical education, and clinical research. We believe that these changes can favorably affect physician well-being without adversely affecting reimbursement.